One or two trainees per workplace for laparoscopic surgery training courses: results from a randomized controlled trial - Kowalewski, Karl-Friedrich; Minassian, Andreas; Hendrie, Jonathan D.; Benner, Laura; Preukschas, Anas; Kenngott, Hannes Götz; Fischer, Lars; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2019)
BackgroundThere are no standards for optimal utilization of workplaces in laparoscopic training. This study aimed to define whether laparoscopy training should be done alone or in pairs (known as dyad training).MethodsThis was a three-arm randomized controlled trial with laparoscopically naïve medical students (n = 100). Intervention groups participated alone (n = 40) or as dyad (n = 40) in a multimodality training curriculum with e-learning, basic, and procedural skills training using box and VR trainers. The control group (n = 20) had no training. Post-performance of a cadaveric porcine laparoscopic cholecystectomy (LC) was measured as the primary outcome by blinded raters using the objective structured assessment of technical skills (OSATS). Global operative assessment of laparoscopic skills (GOALS), time for LC, and VR performances were secondary outcomes.ResultsThere were no differences between groups for performance scores [OSATS: alone (40.2 ± 9.8) vs. dyad (39.8 ± 8.6), p = 0.995; alone vs. control (37.1 ± 7.4), p = 0.548; or dyad vs. control, p = 0.590; and GOALS score: alone (10.6 ± 3.0) vs. dyad (10.0 ± 2.7), p = 0.599; alone vs. control (10.1 ± 3.0), p = 0.748; or dyad vs. control, p = 0.998]. Dyad finished LC faster than control [median = 62.5 min (CI 58.0-73.0) vs. 76.5 min (CI 72.0-80+); p = 0.042], while there were no inter-group differences between alone vs. control [median = 69.0 min (CI 62.0-76.0) vs. control; p = 0.099] or alone vs. dyad (p = 0.840). Dyad and alone showed superior performance on the VR trainer vs. control for time, number of movements, and path length, but not for complications and application of cautery.ConclusionsThe curriculum provided trainees with the laparoscopic skills needed to perform LC safely, irrespective of the number of trainees per workplace. Dyad training reduced the operation time needed for LC. Therefore, dyad training seems to be a promising alternative, especially if training time is limited and resources must be used as efficiently as possible. Trial registration German Clinical Trials Register: DRKS00004675.